Caracterização de genótipos de soja e piramidação de genes Rps para resistência à fitóftora - Santos, Guilherme dos (2022)
Soybean (Glycine max (L.) Merrill) plays a major role in the global commodity scenario. Regarding the biological agents that cause losses in soybean grain yield, there are phytophthora root rot, caused by Phytophthora sojae. One of the most efficient ways to control phytophthora root rot in soybean is genetic resistance. In front of this, this work aimed to characterize phenotypically genotypes carrying Rps genes, as well as the populations generated by the pyramiding of these genes, through the virulence differentiation obtained by inoculation of P. sojae pathotypes. The experiments were divided into stages and conducted in two locations. The phenotypic characterization of the parents carrying Rps genes was carried out in a field experiment in the municipality of Passo Fundo/RS in the 2020/2021 crop season, where phenotypic characteristics and grain yield were evaluated. In the municipality of Cambé/PR, in the years 2020 to 2022, the following steps were carried out in a greenhouse: i) inoculation methodology in seedlings and lateral branches of adult plants in 17 genotypes; ii) hybridizations aiming to combine Rps genes; iii) inoculation and characterization of F1 populations; iv) inoculation and characterization of F2 populations; v) characterization of F2 populations to Rps genes. The characterizations were performed by inoculating the PS2.4, PS14.4, PS34.1, PS36.1 and CMES1608 pathotypes. The results emphasize that inoculations in both seedlings and lateral branches of adult plants allowed genotype characterization for the different pathotypes. Genotypes characterization allowed to identify new possibilities of resistance sources to control P. sojae. Rps pyramiding gene showed to be a great genetic tool for the control of P. sojae. It was possible to identify genotypes reaction and their inoculated progenies with the main pathotypes that cause phytophthora root rot present in Brazilian soils. It was possible to highlight the main Rps genes and their combinations, serving as a basis for new studies and practical applications in soybean breeding programs.